2012
DOI: 10.1111/j.1468-1331.2012.03754.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to respiration influencing survival and respiratory function in patients with amyotrophic lateral sclerosis: a retrospective study

Abstract: Any respiratory abnormality should prompt the clinician to start discussing NIV with the patient. NIV prolongs survival and improves respiratory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…The observed benefits of NIV on pulmonary function decline corroborate previous literature 20 22. While the benefit was significant overall for FVC, FEV 1 , MIP and MEP, we found a wide variability in magnitude of effects across pulmonary function tests and phenotypes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed benefits of NIV on pulmonary function decline corroborate previous literature 20 22. While the benefit was significant overall for FVC, FEV 1 , MIP and MEP, we found a wide variability in magnitude of effects across pulmonary function tests and phenotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, when not accounting for left truncation, observational studies on NIV in MND maybe be biased towards favourable survival in patients who did not use NIV. Therefore, the real survival benefits of NIV may be larger than the reported in previous cohort studies 3 20 22…”
Section: Discussionmentioning
confidence: 90%
“…Of note, the accelerated muscle wasting due to hypermetabolism is bound to involve respiratory muscles. A NIV-related reduction in energy expenditure could therefore theoretically contribute to slow respiratory decline, yet a recent retrospective study suggested, apparently for the first time, that NIV could indeed decrease the ALS-related decline of VC [42]. The correlation observed between REE and FVC and Pi MAX in our patients (Table  3) tends to supports this hypothesis.…”
Section: Discussionsupporting
confidence: 65%
“…In our retrospective study [1], 60 out of 189 patients with amyotrophic lateral sclerosis (ALS) had presented the predominantly bulbar form at disease onset. The disease form was defined according to the patient's history of first symptom and, if there was uncertain history, the patients were assigned in groups according to the predominant clinical signs at first examination (bulbar or pseudobulbar signs versus lower or upper motor neuron deficit on limbs).…”
Section: Sirsmentioning
confidence: 99%